2004
DOI: 10.1248/bpb.27.1207
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Corydalis tuber on Glycine-Induced Ion Current in Acutely Dissociated Rat Periaqueductal Gray Neurons

Abstract: Corydalis tuber is the root of Corydalis yahusuo W. T. WANG classified as Papaveraceae. Aqueous extract from Corydalis tuber is known to stimulate blood circulation and relieve pain. It has traditionally been used for the treatment of neuralgia, dysmenorrhea, and gastrointestinal spasm. 1)The analgesic and spasmolytic properties of the Corydalis tuber are essentially ascribed to several alkaloids: DL-tetrahydropalmatine (THP), D-cotydaline, and corydalis H, I, J, K, and L. The alkaloids exhibited analgesic, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…In addition, Gurwitz (2001) reported that inhibition of glycine transporter in the brain and spinal cord may relieve pain. Recently, it was suggested that the analgesic effects of Oriental medicinal herbs such as Corydalis tuber and Chelidonii herba are closely related to the inhibition on glycine in the PAG neurons (Shin et al, 2003;Cheong et al, 2004). The present results showed the possibility that Bupleuri radix may have an analgesic effect by activating the descending pain control system through the inhibition on glycine-induced ion current in PAG neurons.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…In addition, Gurwitz (2001) reported that inhibition of glycine transporter in the brain and spinal cord may relieve pain. Recently, it was suggested that the analgesic effects of Oriental medicinal herbs such as Corydalis tuber and Chelidonii herba are closely related to the inhibition on glycine in the PAG neurons (Shin et al, 2003;Cheong et al, 2004). The present results showed the possibility that Bupleuri radix may have an analgesic effect by activating the descending pain control system through the inhibition on glycine-induced ion current in PAG neurons.…”
Section: Discussionsupporting
confidence: 54%
“…It is well documented that analgesic action of PAG is mediated by opioid system (Shin et al, 2003;Cheong et al, 2004). Pert and Walter (1976) reported that administration of naloxone, nonselective opioid receptor antagonist, to rats reduced analgesic effect induced by electrical stimulation on the PAG.…”
Section: Discussionmentioning
confidence: 99%
“…Shin et al (2003) demonstrated that Chelidonii herba increases neuronal excitability in PAG, which results in activation of descending pain control system and may contribute as a potential mechanism of the analgesic actions of Chelidonii herba. Cheong et al (2004) also reported that application of Corydalis tuber onto PAG neurons modulates glycine-activated ion current in the PAG neurons, which exerts analgesic action.…”
Section: Discussionmentioning
confidence: 94%
“…Aqueous extract from Corydalis tuber has been used as an analgesic and for the treatment of inflammatory and allergic diseases (Sagare et al, 2000). The analgesic action of Corydalis tuber is closely associated with descending pain control system (Cheong et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Shin et al (2003) demonstrated that Chelidonii herba increases neuronal excitability in PAG, which results in activation of descending pain control system and may contribute as a potential mechanism of the analgesic actions of Chelidonii herba. Cheong et al (2004) also reported that application of Corydalis tuber onto PAG neurons modulates glycine-activated ion current in the PAG neurons, which exerts analgesic action. The SFI derived from walking track analysis in rats provides a reliable and easily quantifiable method for the assessing of motor function after sciatic nerve injury (Varejo et al, 2003).…”
Section: Discussionmentioning
confidence: 94%